PENERAPAN TEKNOLOGI PENGOLAHAN SAGU UNTUK DIVERSIFIKASI PRODUK OLAHAN BERBASIS SAGU DI KECAMATAN MALANGKE BARAT KABUPATEN LUWU UTARA - Andi Mangnguntungi Sudirman; Andi Jumardi; Fitrah Al Anshori; Irmayani Irmayani (Universitas Mataram, 2023)
Sago has excellent potential as a food source but has yet to be utilized optimally. Sago processing in Pao Village, West Malangke District, North Luwu Regency, is still managed using traditional methods. Several problems were found, including the absence of appropriate technology in the sago production process, the need for partners' knowledge for sago diversification, and processed sago products packaged in ordinary containers or plastic bags, causing partners to be unable to meet market demand. The purpose of implementing this PKM is to provide technical skills in using sago processing equipment, increase the ability of partners to diversify processed sago into food ingredients and increase partners' understanding of brands and product labels. At this stage, the PKM implementing team provides outreach to increase partners' knowledge. The second stage is training and assistance in direct practice using tools from executors and materials from partners by demonstrating how to make processed sago products. The results of this PKM implementation: 1) Partners become more knowledgeable and gain new knowledge in making various processed sago diversifications such as sago sticks, brownies and bagea. 2) It becomes easier for partners to use technological tools in making various processed sago diversifications. 3) Partners acquire knowledge on using more hygienic packaging and have branding for sago-based processed products. In addition, 4) Partners become more knowledgeable and gain knowledge in making more modern financial accounting and new knowledge about the Plan business, which can be marketed digitally. Socialization and training in this activity positively influenced participants' knowledge, especially in making processed sago and using packaging.